Genetic diversity and population structure of Saccharomyces cerevisiae strains isolated from different grape varieties and winemaking regions - Schuller, Dorit Elisabeth (2012)
We herein evaluate intraspecific genetic diversity of fermentative vineyard-associated S. cerevisiae strains and evaluate relationships between grape varieties and geographical location on populational structures. From the musts obtained from 288 grape samples, collected from two wine regions (16 vineyards, nine grape varieties), 94 spontaneous fermentations were concluded and 2820 yeast isolates were obtained that belonged mainly (92%) to the species S. cerevisiae. Isolates were classified in 321 strains by the use of ten microsatellite markers. A high strain diversity (8-43 strains per fermentation) was associated with high percentage (60–100%) of fermenting samples per vineyard, whereas a lower percentage of spontaneous fermentations (0–40%) corresponded to a rather low strain diversity (1-10 strains per fermentation). For the majority of the populations, observed heterozygosity (Ho) was about two to five times lower than the expected heterozygosity (He). The inferred ancestry showed a very high degree of admixture and divergence was observed between both grape variety and geographical region. Analysis of molecular variance showed that 81-93% of the total genetic variation existed within populations, while significant differentiation within the groups could be detected. Results from AMOVA analysis and clustering of allelic frequencies agree in the distinction of genetically more dispersed populations from the larger wine region compared to the less extended region. Our data show that grape variety is a driver of populational structures, because vineyards with distinct varieties harbor genetically more differentiated S. cerevisiae populations. Conversely, S. cerevisiae strains from vineyards in close proximity (5-10 km) that contain the same grape variety tend to be less divergent. Populational similarities did not correlate with the distance between vineyards of the two wine regions. Globally, our results show that populations of S. cerevisiae in vineyards may occur locally due to multi-factorial influences, being the grape variety one of them.